Perceptions of Sports Students in the Application of Massive Online Open Course Based on Open Learning Platform - Gilang Nuari Panggraita; Julianur Julianur; Tri Astuti; Ahmad Khafis (STKIP Muhammadiyah Kuningan, 2022)
This study aims to find out more about the perceptions of sports students in the application of the Massive Online Open Course (MOOCs) based on Open Learning in learning. This research method is a qualitative descriptive study. The sampling technique used was purposive sampling with the provisions that semester one and semester three students were registered as active students using the Open Learning platform at Universitas Muhammadiyah Pekajangan Pekalongan and Universitas Muhammadiyah Kalimantan Timur with a total of 84 people. The data collection technique used in this study was a questionnaire in the form of a questionnaire distributed online via Google Form. Furthermore, the data obtained will be analyzed using qualitative descriptive analysis using percentage descriptive statistics. The results showed that students 'perceptions on the implementation aspects of teaching and learning were in the excellent category with a score of 308, the competence aspects of the lecturers were in the excellent class with a score of 317, and the infrastructure aspects were in the medium category with a score of 303. From these three aspects, it can be said that students' perceptions in application Open Learning are in the excellent category with a score of 309. In conclusion, the implementation of teaching and learning and the competence of lecturers in implementing Open Learning based on student perspectives runs well.